Major Choice & Employability in Morocco: English Major as a Case Study - EL AIDA Sara; SABIL Abdelkader (African Scientific Journal, 2022)
The present paper aims to examine the factors that impact students’ choice of English Studies as their college major. Many variables are tested such as gender, age, university, degree, effect of media, employment status, etc. The study explores the employment status and the job opportunities offered to English major graduates in the Moroccan job market. To this end, the bivariate analysis was adopted to analyze quantitative data that was collected through an online survey of 444 students from different universities in Morocco. The quantitative analysis was completed by the results of a qualitative investigation, based on an inductive approach, through three semi-structured interviews. The findings suggest that students choose English as major because they enjoy the learning of the language, and because they think it offers better job opportunities. Another major finding is that the stream background does not affect students’ integration in the Moroccan job market.